Correlation between dietary acid–base load and chronic kidney disease patients with type 2 diabetes mellitus - Huang, Hui; Wang, Qian; Zhang, Ruimin; Liu, Fang; Niu, Yue; Luo, Yayong; Li, Shuang; Li, Tao; Tang, Zhengchun; Wang, Xiaolong; Yang, Jian; Wang, Yong; et al. (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to investigate the effect of dietary acid-base load on patients with chronic kidney disease (CKD) and type 2 diabetes mellitus (T2DM).DesignA total of 300 patients with CKD were enrolled and divided into three groups according to DAL tertiles. Dietary intake was assessed using a 24-h dietary recall, and diet-based acidity was assessed using net endogenous acid production (NEAP), potential renal acid load (PRAL), and dietary acid load (DAL). Multivariable logistic regression models were used to determine the association between diet-based acid load scores and CKD and T2DM.ResultsWithin the food category groupings, the DAL score was positively associated with poultry and eggs and negatively associated with fruits and vegetables. Regarding energy and macronutrients, the DAL score was positively correlated with the intake of protein, animal protein, monounsaturated fatty acids, saturated fatty acids, and fat, while it was negatively correlated with the intake of carbohydrates, plant protein, and dietary fiber. In terms of micronutrients, DAL scores were positively associated with phosphorus intake and negatively associated with potassium, magnesium, and copper intake. After adjusting for age, BMI, energy, and eGFR, and stratifying by sex, logistic regression analysis showed that DAL level (OR = 6.47, 95% CI 1.19–35.18, p = 0.031) was a related factor for CKD and T2DM in females.ConclusionDAL score is a related factor for patients with T2DM and CKD.